Early onset pancreatic malignancies: Clinical characteristics and survival associations. Issue 10 (22nd August 2016) - Beeghly‐Fadiel, Alicia; Luu, Hung N.; Du, Liping; Shi, Chanjuan; McGavic, Dauphne P.; Parikh, Alexander A.; Raskin, Leon
Abstract : Diagnosed before age 50, early onset pancreatic malignancy (EOPM), is hypothesized to be a distinct subset of disease, although research is limited. To better characterize EOPM, and the effect of age at diagnosis on pancreatic cancer survival, we examined clinical characteristics and survival in EOPM and typical age‐at‐onset pancreatic malignancy (TOPM) cases. Vanderbilt University Medical Center (VUMC) Cancer Registry confirmed pancreatic adenocarcinomas (PDACs) and malignant pancreatic neuroendocrine tumors (PNETs) were evaluated. Clinical characteristics were compared using χ 2 tests. Overall survival was visualized with Kaplan–Meier functions; Cox proportional hazards regression was used to evaluate hazard ratios (HRs) and 95% confidence intervals (CIs). A total of 1, 697 pancreatic malignancies were diagnosed at the VUMC between 1988 and 2013. Of 1, 407 PDACs, 118 (8.4%) were EOPM, which was associated with significantly better survival (adjusted HR: 0.82, 95% CI: 0.67–1.00). EOPM and TOPM PDACs significantly differed with regard to having multiple malignancies; survival associations significantly differed by race, stage of disease, treatment and multiple malignancies. Of 190 PNETs, 63 (33.1%) were EOPM, which was not significantly associated with survival (adjusted HR: 0.80, 95% CI: 0.46–1.40). Malignant neuroendocrine EOPM and TOPM cases significantly differed by stage of disease and tumor location; survival associations significantly differed by family history of pancreatic cancer, stage of disease and multiple malignancies. Differences in clinical characteristics and associations with survival were identified, indicating that EOPM is distinct from TOPM, and exists among both pancreatic adenocarcinomas and malignant pancreatic neuroendocrine tumors. Abstract : What's new? Pancreatic cancer that occurs before age 50 has not been well characterized. In this study, the authors compared survival and clinical characteristics in early‐onset vs . typical age‐at‐onset pancreatic cancers. They found that in pancreatic adenocarcinoma (PDAC), early onset confers significant survival advantage. This and differences in clinical characteristics for both PDACs and malignant pancreatic neuroendocrine tumors (PNETs) support the hypothesis that early onset pancreatic malignancy (EOPM) is a distinct subset of pancreatic cancers.